PENINGKATAN AKUNTANSI DAN EFISIENSI KEUANGAN MELALUI PENDAMPINGAN DIGITAL BAGI UMKM WAROENG MESSO DI KABUPATEN GOWA - Tuti Supatminingsih; Andi Asti Handayani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This article discusses "Increasing Accounting and Financial Efficiency Through Digital Assistance for Waroeng Messo MSMEs in Gowa Regency". This research aims to explore how digital assistance can improve accounting and financial efficiency for MSMEs, especially Waroeng Messo in Gowa Regency. Through an information technology approach, this research provides new insights in increasing financial literacy and the application of technology for MSMEs. The research method includes a preparation stage with direct visits to MSMEs business actors to identify the problems they face. The research results show that the use of information technology-based applications/software can provide significant benefits for MSMEs, such as saving time, speeding up work, and securing data. In conclusion, digital assistance can be an effective solution in increasing the accounting and financial efficiency of MSMEs, with government support that encourages the growth of the MSMEs sector.